A Legacy of Canadian Cultural Tradition and the Small Press:: The Case of Talonbooks - Scherf, Kathleen (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
According to the Association of Book Publishers of British Columbia, the most editorially and financially active of the surviving Canadian literary presses is Talonbooks. While Talonbooks's primary significance lies in its activity as a publisher of Canadian literature, particularly drama, the existence and survival of Talonbooks is of great scholarly interest because the life of the company closely documents and reflects the life of Canadian literary culture since 1967 with a west coast twist. From the beginning, Talonbooks has taken an editorial position of difference, separating itself from and publishing against the geographical and perceived intellectual center of Canadian letters; it sought not only to express but also to serve the local. Correspondence from most of the press's early writers reveals the extent of their participation in book design. The press faced financial challenges during the 1970s. The professionalization of its business practices and the press's maturing involvement in the politics of the Canadian publishing industry mark its movement into the domestic publishing establishment.